Cardiovascular and Gas Exchange Effects of Individualized Positive End-Expiratory Pressures in Cats Anesthetized With Isoflurane - Machado, Marcela L.; Soares, Joao H. N.; Pypendop, Bruno H.; Aguiar, Antonio J. A.; Braun, Christina; Motta-Ribeiro, Gabriel C.; Jandre, Frederico C. (Frontiers in Veterinary Science, 2022)
Objectives To compare the effects of four levels of end-expiratory pressure [zero (ZEEP) and three levels of positive end-expiratory pressure (PEEP)] on the cardiovascular system and gas exchange of cats anesthetized with isoflurane and mechanically ventilated for 3 h with a tidal volume of 10 ml/kg. Study Design Prospective, randomized, controlled trial. Animals Six healthy male neutered purpose-bred cats. Methods Anesthesia was induced with isoflurane and maintained at 1.3 minimum alveolar concentration. PEEP of maximal respiratory compliance (PEEPmaxCrs) was identified in a decremental PEEP titration, and cats were randomly ventilated for 3 h with one of the following end-expiratory pressures: ZEEP, PEEPmaxCrs minus 2 cmH2O (PEEPmaxCrs−2), PEEPmaxCrs, and PEEPmaxCrs plus 2 cmH2O (PEEPmaxCrs+2). Cardiovascular and gas exchange variables were recorded at 5, 30, 60, 120, and 180 min (T5 to T180, respectively) of ventilation and compared between and within ventilation treatments with mixed-model ANOVA followed by Dunnet's and Tukey's tests (normal distribution) or Friedman test followed by the Dunn's test (non-normal distribution). Significance to reject the null hypothesis was considered p < 0.05. Results Mean arterial pressure (MAP—mmHg) was lower in PEEPmaxCrs+2 [63 (49–69); median (range)] when compared to ZEEP [71 (67–113)] at T5 and stroke index (ml/beat/kg) was lower in PEEPmaxCrs+2 (0.70 ± 0.20; mean ± SD) than in ZEEP (0.90 ± 0.20) at T60. Cardiac index, oxygen delivery index (DO2I), systemic vascular resistance index, and shunt fraction were not significantly different between treatments. The ratio between arterial partial pressure and inspired concentration of oxygen (PaO2/FIO2) was lower in ZEEP than in the PEEP treatments at various time points. At T180, DO2I was higher when compared to T5 in PEEPmaxCrs. Dopamine was required to maintain MAP higher than 60 mmHg in one cat during PEEPmaxCrs and in three cats during PEEPmaxCrs+2. Conclusion In cats anesthetized with isoflurane and mechanically ventilated for 3 h, all levels of PEEP mildly improved gas exchange with no significant difference in DO2I when compared to ZEEP. The PEEP levels higher than PEEPmaxCrs−2 caused more cardiovascular depression, and dopamine was an effective treatment. A temporal increase in DO2I was observed in the cats ventilated with PEEPmaxCrs. The effects of these levels of PEEP on respiratory mechanics, ventilation-induced lung injury, as well as in obese and critically ill cats deserve future investigation for a better understanding of the clinical use of PEEP in this species.